2022
DOI: 10.1002/jcla.24806
|View full text |Cite
|
Sign up to set email alerts
|

Association between KRAS gene polymorphisms and genetic susceptibility to breast cancer in a Chinese population

Abstract: Objective The KRAS gene has a pathophysiological role in the development of many cancers. This study aims to investigate the relationship between KRAS polymorphisms and genetic susceptibility to breast cancer. Method The rs712, rs12587 and rs9266 gene loci in the KRAS gene of 421 subjects (141 breast cancer patients, 141 benign breast tumours and 139 healthy controls) were analysed by the polymerase chain reaction and SNaPshot sequencing. Transcriptomic information on KRAS and corresponding clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…protein domains have been predicted as frequently mutated domains and reported in the DCMP database. Protein Domain Target Function Reference BCL-2* Anti-apoptotic protein Apoptosis [ 191 ] CDK4/6 Cyclin-dependent kinases Cell cycle regulation [ 192 ] EGFR Epidermal growth factor receptor Cell proliferation, angiogenesis [ 193 ] FLT3* FMS-like tyrosine kinase 3 Cell survival, proliferation [ 194 ] HER2 Human epidermal growth factor receptor 2 Cell proliferation, survival [ 195 ] IDH1 Isocitrate dehydrogenase 1 Metabolic reprogramming [ 196 ] JAK2 Janus kinase 2 Cell proliferation, differentiation [ 197 ] KRAS Kirsten rat sarcoma viral oncogene homolog Cell proliferation, survival [ 198 ] mTOR Mammalian target of rapamycin Cell growth, metabolism [ 199 ] NTRK Neurotrophic tyrosine receptor kinase Cell survival, differentiation [ 200 ] PD-L1 Programmed death-ligand 1 …”
Section: Mechanisms Underlying the Impact Of Protein Domain Mutations...mentioning
confidence: 99%
“…protein domains have been predicted as frequently mutated domains and reported in the DCMP database. Protein Domain Target Function Reference BCL-2* Anti-apoptotic protein Apoptosis [ 191 ] CDK4/6 Cyclin-dependent kinases Cell cycle regulation [ 192 ] EGFR Epidermal growth factor receptor Cell proliferation, angiogenesis [ 193 ] FLT3* FMS-like tyrosine kinase 3 Cell survival, proliferation [ 194 ] HER2 Human epidermal growth factor receptor 2 Cell proliferation, survival [ 195 ] IDH1 Isocitrate dehydrogenase 1 Metabolic reprogramming [ 196 ] JAK2 Janus kinase 2 Cell proliferation, differentiation [ 197 ] KRAS Kirsten rat sarcoma viral oncogene homolog Cell proliferation, survival [ 198 ] mTOR Mammalian target of rapamycin Cell growth, metabolism [ 199 ] NTRK Neurotrophic tyrosine receptor kinase Cell survival, differentiation [ 200 ] PD-L1 Programmed death-ligand 1 …”
Section: Mechanisms Underlying the Impact Of Protein Domain Mutations...mentioning
confidence: 99%
“…Therefore, the variants analyzed in this study are present in mature mRNA and may play an important role in gene expression regulation via interactions with miRNAs [10]. Several studies have shown the association between SNVs present in the 3 UTR region of the KRAS gene and various types of cancer, including breast cancer, Wilms tumors, colorectal cancer, and glioma, among others [11][12][13][14][15][16][17]. According to the NIH SNP database, SNV rs12587 is located at chr12:25205894 (GRCh38.p14) and represents T > G transversion, whereas rs8720 is located at chr12:25206009 (GRCh38.p13) and entails the transition T > C. On the one hand, SNV rs12587 has been associated with Wilms tumor [12] and glioma [18], but it has not been associated with CRC [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we experimentally and in silico analyzed two SNVs, rs12587 and rs8720, both located in the 3 UTR region of the KRAS gene, a crucial regulatory region for gene expression. Numerous studies indicate that the post-transcriptional regulation of KRAS is mediated in this region by various miRNAs, suggesting that these variants may potentially interfere with its regulation [9,12,14,15]. These variants have been studied and associated with different types of cancer in diverse populations but not in the Mexican population, where studies on the association between KRAS gene variants and colorectal cancer are limited.…”
Section: Introductionmentioning
confidence: 99%